2018
DOI: 10.4025/actascibiolsci.v40i1.37528
|View full text |Cite
|
Sign up to set email alerts
|

<b>Anatomical description of the salivary glands: parotid, mandibular and sublingual of the crab-eating-fox (<i>Cerdocyon thous</i>)

Abstract: Descriptive anatomical studies of wild animals are fundamental, since they provide subsidies for the elaboration of more adequate techniques of sustained management, contributing to the preservation of species threatened with extinction. Thus, the aim of the study is to anatomically describe the salivary glands: parotid, mandibular and sublingual of the crab-eating-fox (Cerdocyon thous). For this purpose, three carcasses of crab-eating-fox donated by Ibama were used. The animals were fixed with 10% aqueous for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
5
6
0
Order By: Relevance
“…The morphological and topographic attributes of the puma mandibular gland corroborate numerous aspects with other domestic carnivorous mammals, such as dogs, cats (18,20) and wild carnivores, such as the undersea, coati (16) and crab-eatingfox (7) . However, we observed some discordant anatomical characteristics compared to other wild and domestic species.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The morphological and topographic attributes of the puma mandibular gland corroborate numerous aspects with other domestic carnivorous mammals, such as dogs, cats (18,20) and wild carnivores, such as the undersea, coati (16) and crab-eatingfox (7) . However, we observed some discordant anatomical characteristics compared to other wild and domestic species.…”
Section: Discussionsupporting
confidence: 62%
“…Based on the dissections, the anatomical attributes of the parotid gland of the puma resemble morphologically in some respects to other wild and domestic carnivorous mammals. The location of the parotid salivary gland in the caudal-dorsal region of the face, ventrally arranged the basal region of the auricular cartilage, is analogous to that found in some wild carnivorous mammals such as crab-eating-fox (7) , crab eating raccoon (15) and coati (16) . In addition, these authors also found a fissure in the dorsal end of the gland, which is similar to that found in the puma in our study.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations